Для всех выражений будем применять раскрытия квадрата разности/суммы.
Для суммы:
Для разности:
1)
2)
3)
4)
Для всех выражений будем применять раскрытия квадрата разности/суммы.
Для суммы:![(x+y)^{2} =x^{2} +2xy+y^{2}](/tpl/images/0508/2672/ece30.png)
Для разности:![(x-y)^{2} =x^{2} -2xy+y^{2}](/tpl/images/0508/2672/2a5dc.png)
1)![(2x+6)^2=(2x)^{2} +2*2x*6+6^{2} =4x^{2} +24x=36](/tpl/images/0508/2672/d67b4.png)
2)![(y^2-3)^2=(y^{2} )^{2} -2*y^{2} *3+3^{2} =y^{4} -6y^{2} +9](/tpl/images/0508/2672/270db.png)
3)![(5x+6y)^2=(5x)^{2} +2*5x*6y+(6y)^{2} =25x^{2} +60xy+36y^{2}](/tpl/images/0508/2672/c5749.png)
4)![(x^2-2y)^2=(x^{2} )^{2} -2*x^{2} *2y+(2y)^{2} =x^{4} -4x^{2} y+4y^{2}](/tpl/images/0508/2672/a9ab7.png)